Flap Impaling: A Simple and Effective Technique in Soft Tissue Reconstruction of Complex Extremity Wounds - Jayaraman, Sathish Kumar; Chellamuthu, Abiramie; Venugopal, Srinivasan; Vasudevan, Vishnu Priya (Indian Journal of Plastic Surgery, 2025)
Composite defects due to trauma present with compound comminuted fractures with soft tissue loss. Stabilization requires multiple Schanz pins across the fracture segments and flap cover for soft tissue reconstruction. These pins hinder flap inset and may require complex planning with multiple flaps. A simple approach is to impale the flaps over these pins to achieve flap inset without disturbing the skeletal fixation. This method of impaling was utilized for free as well as pedicled fasciocutaneous and muscle flaps. A stab incision is made and careful dissection is done to create a passage for the pins without injuring the vascularity of these flaps. In this manner multiple pins can be passed as needed. Flap inset is then completed. Slight modifications in threading the pins are required depending on whether a free or a pedicled flap is used. This study includes 16 flaps of which 15 were for lower limbs and 1 was for upper limb reconstruction. Pedicled flaps used were 13, the most common being inferiorly based fasciocutaneous flaps. Free flaps used were three, which included two muscle flaps and one fasciocutaneous flap. Two flaps were impaled in three places. All the flaps survived without any loss. Suture line dehiscence in four flaps was managed conservatively. Impaling the flaps on Schanz pins is a simple procedure to achieve soft tissue reconstruction in compound defects. Knowledge of the vascular anatomy and blood supply of the flaps is imperative in protecting the pedicle and maintaining the vascularity.
Keywords: flap impaling; soft tissue reconstruction; compound defects; free flaps